2020
DOI: 10.1534/genetics.120.303626
|View full text |Cite
|
Sign up to set email alerts
|

Evolved Differences in cis and trans Regulation Between the Maternal and Zygotic mRNA Complements in the Drosophila Embryo

Abstract: How gene expression can evolve depends on the mechanisms driving gene expression. Gene expression is controlled in different ways in different developmental stages; here we ask whether different developmental stages show different patterns of regulatory evolution. To explore the mode of regulatory evolution, we used the early stages of embryonic development controlled by two different genomes, that of the mother and that of the zygote. During embryogenesis in all animals, initial developmental processes are dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 90 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…We found that the number of genes with compensatory regulatory modifications increases sharply after gastrulation, indicating that gene expression may be more tightly controlled past that point. Studies across Drosophila species, for example, have indicated that maternal effects are regulated differently than zygotic effects, but in this case there are larger trans -acting factors in early (maternally controlled) developmental stages (Cartwright and Lott 2020). We do not see such a clear effect; trans -acting factors make up most of the regulatory architecture throughout development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the number of genes with compensatory regulatory modifications increases sharply after gastrulation, indicating that gene expression may be more tightly controlled past that point. Studies across Drosophila species, for example, have indicated that maternal effects are regulated differently than zygotic effects, but in this case there are larger trans -acting factors in early (maternally controlled) developmental stages (Cartwright and Lott 2020). We do not see such a clear effect; trans -acting factors make up most of the regulatory architecture throughout development.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially a few trans -acting regulatory modifications, such as changes to transcription factors, could account for most of the developmental and phenotypic differences between morphs. As species divergence time increases, cis -acting elements can arise and refine gene expression of individual genes (Coolon et al 2014; Cartwright and Lott 2020; Wittkopp et al 2004). These regulatory architecture trends have been reported in other species, but none have examined the short evolutionary window of divergent morphs within the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Further, just a handful of genes have complete GOF or LOF expression phenotypes. These results suggest that the accessory gland is not prone to widespread dysgenesis between these species, in contrast to results from Drosophila testis or female whole-animal data (Ranz et al 2004;Haerty and Singh 2006;Moehring, Teeter, and Noor 2007;McManus et al 2010;Coolon et al 2014;Cartwright and Lott 2020;Ranz et al 2023), Caenorhabditis data (Sánchez-Ramírez et al 2021), mouse liver (Goncalves et al 2012) and testis (Mack, Campbell, and Nachman 2016) data. Thus, our transcriptomic data are consistent with the observations of Stumm-Zollinger and Chen (1988), that hybrid accessory glands have relatively normal morphology, seminal fluid, and ability to induce the female PMR.…”
Section: Discussionmentioning
confidence: 53%
“…Variation in maternal mRNA deposition can certainly occur within a species, particularly due to maternal condition or genotype. For example, in Drosophila melanogaster the difference in oocyte gene expression between extreme maternal environmental conditions (starved mothers fed 5% of control mothers’ diet) is ~ 1.8% [ 62 , 63 ]. Another study, which sampled a much greater amount of genetic diversity, found maternal mRNA from embryos within populations of D. melanogaster to be much greater (40–60% of expressed genes differentially expressed; [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of our cross design is that we can determine the mode of regulation for differentially expressed genes. Typically regulatory analyses of cis and trans acting factors are conducted in hybrids [ 38 41 , 63 , 84 ], however, we were able to carry out these analyses in intraspecific comparisons with the caveat that there are fewer distinguishing polymorphisms between the alleles of the two parents. As such, we focus on the genes that are differentially expressed between the two morphs and therefore are not capturing the genetic architecture of genome-wide divergence between morphs, but rather the mode of regulation of genes that are differently expressed.…”
Section: Discussionmentioning
confidence: 99%